The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/molecules26144257
|View full text |Cite
|
Sign up to set email alerts
|

New In Vitro-In Silico Approach for the Prediction of In Vivo Performance of Drug Combinations

Abstract: Pharmacokinetic (PK) studies improve the design of dosing regimens in preclinical and clinical settings. In complex diseases like cancer, single-agent approaches are often insufficient for an effective treatment, and drug combination therapies can be implemented. In this work, in silico PK models were developed based on in vitro assays results, with the goal of predicting the in vivo performance of drug combinations in the context of cancer therapy. Combinations of reference drugs for cancer treatment, gemcita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…In a study from our group, gemcitabine and 5-fluorouracil (5-FU), which is another traditional anticancer drug, were combined with three repurposed drugs, itraconazole, verapamil, and tacrine to assess their joined effect on cancerous cells. The main objective was to predict the effect of these combinations in humans using in vitro and in silico techniques [ 27 ].…”
Section: Combination Of Gemcitabine With Repurposed Drugsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study from our group, gemcitabine and 5-fluorouracil (5-FU), which is another traditional anticancer drug, were combined with three repurposed drugs, itraconazole, verapamil, and tacrine to assess their joined effect on cancerous cells. The main objective was to predict the effect of these combinations in humans using in vitro and in silico techniques [ 27 ].…”
Section: Combination Of Gemcitabine With Repurposed Drugsmentioning
confidence: 99%
“…The results showed that combinations with verapamil and tacrine had no effects on all types of cells, with the effects being the same as the ones with the anticancer drug alone, while combination with itraconazole improved the overall effect with 5-FU in all cell types and with gemcitabine in A549 cells. However, when looking at the effects of gemcitabine in PNT2 and PC-3 cells, the increase was only noticeable for smaller concentrations of this drug, matching with the control at higher concentrations of gemcitabine [ 27 ].…”
Section: Combination Of Gemcitabine With Repurposed Drugsmentioning
confidence: 99%
See 3 more Smart Citations